A Correlational Study of Gadget Used Towards Reading Interest - Siti Chadijah; Nur Syariatin; Yuli Rohmiyati; Jepri Utomo; Arief Yanto Rukmana (Journal of English Culture, Language, Literature and Education, 2023)
The purpose of this study was to determine the relationship between the use of gadgets and reading interest of class XII students in one of the high schools. The approach in this study uses descriptive quantitative methods with a correlation approach. The population of this study were all XII grade students and the sample used was 30 students. The technique used in sampling is proportional stratified random sampling. Data collection was carried out using questionnaires, observation and documentation. Variable measurement was carried out using a questionnaire with a Likert scale. The data analysis technique is descriptive analysis and correlation test. The results of this study found that there is a relationship, where the use of smartphones affects students' reading interest. Based on the result the product moment correlation test analysis with a value of X ̅ = 67,77 and Y ̅ = 80,4 resulting in r = 0,949 meaning that there is a significant correlation between gadget used toward reading interest. This evidenced by the value of the product moment coefficient which shows that r> 0.01. Therefore, Teachers/parents are expected to be able to minimise students' gadget use, in addition, the role of teachers/parents in motivating providing reading materials or reading activities can be one aspect of supporting students' interest in reading.